Studi Adsorpsi Logam Berat Besi (Fe) dan Timbal (Pb) Air Sungai Mahakam oleh Limbah Cangkang Telur dan Abu Gosok - Alris Sanca Pratama Putra; Rahmawati Munir; Adrianus Inu Natalisanto (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2022)
Waste could be found easily anywhere such as eggshells and rubbing-ash. Being a non-usable rubbish, These type of waste can be usefull in someways with a right treatment and deep research on compound material with in. The physical content from these waste utilized to be an adsorbent, it adsorbs a metal content e.g Mahakam river water sample. Main purpose of this research was based on benefical content from eggshells and rubbing-ash as their ability decreasing metal content. This study concluded experimentally using adsorbtion methods, a device such as Atomic Absobtion Spectrophotometer (AAS) was used to test the decreasing effect on logam content. The obtained data from testing process used to analyzed a metal concentration that disolved in water sample. This study results on decreasing metal concentration such as Fe and also Pb on Mahakam river water sample. Fe concentrat on these water sample shows decline rate from 1,5 mg/L to 0,11 mg/L given certain treatment adding eggshels powder. And also Pb content reduced from 1,69 mg/L to 0,24 mg/L indicate a little waste content from treated water sample. Inference from this study suggest addition of eggshells and rubbing-ash waste in form of powder had decreasing-effect on soluble metal content from Mahakam River water sample.